The Ability of Banks to Lend to Informationally Opaque Small Businesses - Berger, Allen N.; Klapper, Leora; Udell, Gregory F. (World Bank, Washington, DC, 2014)
Consolidation of the banking industry is shifting assets into larger institutions that often operate in many nations. Large international financial institutions are geared toward serving large wholesale customers. How does this affect the banking system's ability to lend to informationally opaque small businesses? The authors test hypotheses about the effects of bank size, foreign ownership, and distress on lending to informationally opaque small firms, using a rich new data set on Argentinean banks, firms, and loans. They also test hypotheses about borrowing from a single bank versus borrowing from several banks. Their results suggest that large and foreign-owned institutions may have difficulty extending relationship loans to opaque small firms, especially if small businesses are delinquent in repaying their loans. Bank distress resulting from lax prudential supervision and regulation appears to have no greater effect on small borrowers than on large borrowers, although even small firms may react to bank distress by borrowing from multiple banks, despite raising borrowing costs and destroying some of the benefits of exclusive lending relationships.